The untapped potentials of EMI programmes. The Dutch case. (December 2021) - Wilkinson, Robert; Gabriëls, René
Abstract: Despite the enormous expansion of EMI research, the potential of students' multilingualism remains unacknowledged. The challenge is not to neglect this multilingualism that includes the different languages students master and their access to language-related knowledge resources. Therefore, this study aimed to unravel students' multilingualism as a resource. It explores the range of language competences in three consecutive cohorts of EMI students at a Dutch university (total 342). Using a questionnaire and focus groups, the study reveals respondents speaking at least two or three additional languages. Reported competence is high in L1 and L2, but declines sharply in L3, L4 and L5. Results suggest scope for additional language learning and sufficient potential for expanding additional language use in EMI programmes. The challenge is to incorporate multilingualism in EMI. Students' linguistic repertoires have the potential to convey knowledge to speakers of a specific language and elaborate nuances that many English L2 speakers report missing in English-only programmes. This might improve the quality of education. However, the multilingual challenge in EMI confronts the paradox that the more a cohort becomes linguistically and culturally diverse, the greater the pressures to converge on a single medium of communication.